Poetics Of The Epistles Of Sirojiddin Seyyid - Doshanova Guljakhan Ismailovna (Genius Journals, 2025)
This article provides an in-depth analysis of the unique characteristics of lyrical-epic imagery in the works of Sirojiddin Sayyid. The author’s creative works combine a distinct lyrical spirit with an epic scale, forming a unique literary approach within Uzbek literature. Sayyid's epics harmoniously depict national values and human emotions, where the inner world of lyrical heroes is intertwined with the sequence of epic events, portraying their feelings, goals, and struggles in a profound way
Keywords: Sirojiddin; lyrical-epic imagery; epics